Leadership of Assessment, Inclusion, and Learning - Scott, Shelleyann; Scott, Donald E.; Webber, Charles F. (The Enabling Power of Assessment, 2016)
This book provides pragmatic strategies and models for student assessment and ameliorates the heightened sense of confusion that too many educators and leaders experience around the complexities associated with assessment. In particular, it offers guidance to school and district personnel charged with fair and appropriate assessment of students who represent a wide variety of abilities and cultures. Chapters focus on issues that directly impact the educational lives of teachers, students, parents, and caregivers. Importantly, the confluence of assessment practices and community expectations also are highlighted. Assessment is highly politicised in contemporary society and this book will both confirm and challenge readers' beliefs and practices. Indeed, discerning readers will understand that the chapters offer them a bridge from many established assessment paradigms to pragmatic, ethical solutions that align with current expectations for schools and districts. In Part One, readers engage with concepts and skills needed by school learning leaders to guide optimal assessment practices. Part Two delves into student assessment within and across disciplines. Part Three provides pragmatic approaches that address assessment in the context of inclusive intercultural education, pluralism, and globalisation.